Speaking anxiety in EFL learners: A systematic review of causes, strategies, and pedagogical interventions - Gunawan, Iwan Dudy (EduLite: Journal of English Education, Literature and Culture, 2026)
Speaking anxiety remains a persistent challenge for English as a Foreign Language (EFL) learners, particularly in contexts where opportunities for authentic oral communication are limited. The goal of this study is to synthesize contemporary research on the causes of speaking anxiety among EFL learners, the effectiveness of pedagogical interventions, and their classroom implications. This study employed a systematic literature review (SLR) design by analyzing 20 peer-reviewed articles from Scopus-indexed journals published between 2020 and 2025, supported by 27 additional relevant sources. The analysis employed thematic synthesis informed by established theoretical frameworks, including the Affective Filter Hypothesis, Self-Efficacy Theory, Social Constructivism, and Communicative Language Teaching. The findings indicate that speaking anxiety is primarily driven by fear of negative evaluation, low self-confidence, unsupportive classroom environments, linguistic insecurity, and sociocultural norms. The review further reveals that technology-enhanced approaches, drama-based activities, flipped classrooms, digital storytelling, and collaborative learning consistently contribute to anxiety reduction when accompanied by emotional support from teachers. This review contributes to the field by bridging the gap between theoretical perspectives and classroom practices, particularly in underrepresented Southeast Asian EFL contexts. It highlights the importance of emotionally safe, learner-centered, and culturally responsive instructional designs. The study concludes by recommending longitudinal and cross-cultural research to strengthen the sustainable implementation of anxiety-reducing pedagogical interventions in diverse EFL settings.